Презентация лаборатории ИТСМЗ Польша - Белоус, Н. В. (My University, 2009)
Презентация возможностей НУЛ ИТСМЗ в: Program environment for learning and testing any discipline Estimation of quality analysis of test items and definition of the item discrimination and ability parameters
Keywords: научная учебная лаборатория